2009
DOI: 10.1063/1.3269590
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced transformation in FeMnGa alloys

Abstract: A kind of ferromagnetic shape memory alloy with off-stoichiometric composition of Heusler alloy Fe 2 MnGa has been synthesized. By optimizing composition, the martensitic transformation has been modified to occur at about 163 K accompanying spontaneous magnetization, which enables a magnetic field-induced structural transition from a paramagnetic parent phase to a ferromagnetic martensite with high magnetization of 93.8 emu/g. The material performs a quite large lattice distortion through the transformation, ͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 23 publications
2
47
0
6
Order By: Relevance
“…Значний інтерес до стехіометричних та нестехіометричних стопів Fe 2 MnGa обумовлено відкриттям у цих стопів властивостей, що можуть знайти практичне застосування, а саме, значної обмінної анізотропії [1][2][3], метамагнетного фазового перетворення з антифе-ромагнетної (АФМ) фази в феромагнетну (ФМ) [1][2][3][4], мартенситно-го перетворення [5][6][7][8][9]. Танг та ін.…”
Section: вступunclassified
See 2 more Smart Citations
“…Значний інтерес до стехіометричних та нестехіометричних стопів Fe 2 MnGa обумовлено відкриттям у цих стопів властивостей, що можуть знайти практичне застосування, а саме, значної обмінної анізотропії [1][2][3], метамагнетного фазового перетворення з антифе-ромагнетної (АФМ) фази в феромагнетну (ФМ) [1][2][3][4], мартенситно-го перетворення [5][6][7][8][9]. Танг та ін.…”
Section: вступunclassified
“…запропонували керувати величи-ною обмінної анізотропії в нестехіометричних однофазних (ГЦК) стрічках стопу Fe-Mn-Ga, що були одержані гартуванням з рідкої фази, шляхом термомагнетного оброблення стрічок, яке викликало зміну вмісту АФМ-та ФМ-фаз в стопі при метамагнетному перетво-ренні [2]. В той же час відомо, що стоп Fe 2 MnGa, композиція якого незначно відрізняється від стехіометричної, може бути як двофаз-ним і містити ГЦК (АФМ при низьких температурах та незначних зовнішніх магнетних полях) та ОЦК (феромагнетну при Т  190 К) фази, так може містити і лише ОЦК-фазу [4,5,10]. Таким чином, для двофазних стопів Fe 2 MnGa можна очікувати ускладнені магне-тні властивості, які виявляють риси обох фаз.…”
Section: вступunclassified
See 1 more Smart Citation
“…Recently, a number of research groups have reported three different kinds of ferrous SMAs, Fe-Ni-Co-Al-based alloys (from fcc to bct) [9][10][11][12][13][14][15][16][17][18][19][20], Fe-Mn-Ga alloy (from L2 1 to D0 22 ) [21,22], and Fe-Mn-Al-Ni alloy (from bcc to nano-twinned fcc) [23][24][25][26][27][28], showing thermoelastic transformation. In case of the Fe-Ni-Co-Al-based and Fe-MnAl-Ni alloys, strengthening of the parent phase resulting from fine and coherent precipitates of the c 0 phase with the L1 2 structure and the b phase with the B2 structure by aging heat treatment are important to realize thermoelastic transformation and SE properties, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast the c/a ratio of the equilibrium low temperature phase in stoichiometric Fe 2 MnGa is 0.927 and the transformation is associated with a volume change of +1.35% [6]. Annealed off-stoichiometric polycrystals (Fe 50 Mn 22.5 Ga 27.5 ) were recently shown to have a dramatic 2 magnetic-field induced strain with a theoretical performance up to (c − a)/c = 33.5% [7].…”
Section: Introductionmentioning
confidence: 99%